2020
DOI: 10.3390/healthcare8020124
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Dental Care Needs among Korean National Health Insurance Beneficiaries Based on Income Inequalities: Results from Five Waves of a Population-Based Panel Study

Abstract: This study investigates whether self-employed beneficiaries experience greater difficulties in accessing dental care than insured employees based on their income level. This analysis uses 2011–2015 data from the Korea Health Panel, a population-based and nationally representative sample, covering 7083 participants aged 18 years and older. We measured barriers to dental access based on unmet needs or the inability to receive necessary dental care owing to the past year’s economic burdens. The type of health ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, homeless and low-income groups have reported a higher rate of unmet dental care needs in other South Korean studies (Sohn et al, 2020). Although national health insurance and MA cover essential services, the rate of out-of-pocket payment for dental care TA B L E 2 Association between unmet dental care needs and respondents' characteristics services is still 81.9% in South Korea (Sohn et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…However, homeless and low-income groups have reported a higher rate of unmet dental care needs in other South Korean studies (Sohn et al, 2020). Although national health insurance and MA cover essential services, the rate of out-of-pocket payment for dental care TA B L E 2 Association between unmet dental care needs and respondents' characteristics services is still 81.9% in South Korea (Sohn et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…However, household income level also showed a significant association with total perceived unmet dental needs (including financial reasons and time scarcity)—but only in women. Income is a well-established predisposing factor for unmet dental needs according to previous Korean studies [ 2 , 9 , 10 ] and many studies reported that women reported more perceived unmet dental needs than men [ 7 , 9 , 10 ]. However, the evidence on gender differences in the association between income and unmet dental care has been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The enabling domain includes personal/family resources, while the need domain includes perceived and evaluated need [ 6 ]. Previous Korean studies have found a correlation between perceived unmet dental care needs and (1) predisposing variables such as younger age, female gender, marital status, and low education level [ 2 , 7 ]; (2) enabling variables such as income, engagement in precarious work, unemployment, medical aid as a type of insurance, and long working hours [ 2 , 8 , 9 , 10 , 11 ], and (3) need factors such as poor oral health status [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, MA beneficiaries persistently experienced unmet healthcare needs, despite a lower risk of catastrophic health expenditure relative to other groups, because they did not have to make deductible payments, which forced them to limit medical services availed because of the deduction ceiling. It has also been confirmed that the lowest income and self-deployed benefits are more likely to experience unmet dental needs in the dental field of Korea [ 28 ]. Recently, Moon Care allowed for increased insurance coverage aimed to mitigate catastrophic health expenditure and unmet healthcare needs.…”
Section: Discussionmentioning
confidence: 99%